1997
DOI: 10.1046/j.1365-2567.1997.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope specificity of IgE antibodies to a major allergen (Cry j 1) of Japanese cedar pollen in sera of humans and monkeys with pollinosis

Abstract: Japanese cedar (Cryptomeria japonica) pollinosis has been reported to occur naturally in Japanese monkeys (Macaca fuscata) as well as humans. Using monoclonal antibodies (mAb) specific to Cry j 1, a major allergen in Japanese cedar pollen, we identified five independent epitopes (EP‐1 to EP‐5) on the molecule. The epitopes recognized by IgE antibodies in the sera of humans and monkeys with the pollinosis were analysed by an IgE enzyme‐linked immunosorbent assay inhibition method with these mAb. In human patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…However, since none of the five known allergenic homologues of Cry j 1 share this glycosylation site (Midoro-Horiuti et al, 2001;Aceituno et al, 2000;Suzuki et al, 1996;Sone et al, 1994), this epitope cannot be shared with the other known cedar allergens (Midoro-Horiuti et al, 1992;Schwietz et al, 2000). The presence of additional IgE epitopes on Cry j 1 was demonstrated by the finding that three unique groups of anti-Cry j 1 mAbs inhibited the binding to Cry j 1 of IgE from the sera of patients with Japanese cedar hypersensitivity (Sakaguchi et al, 1997). However, these epitopes have not been localized to specific structural elements or regions of Cry j 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, since none of the five known allergenic homologues of Cry j 1 share this glycosylation site (Midoro-Horiuti et al, 2001;Aceituno et al, 2000;Suzuki et al, 1996;Sone et al, 1994), this epitope cannot be shared with the other known cedar allergens (Midoro-Horiuti et al, 1992;Schwietz et al, 2000). The presence of additional IgE epitopes on Cry j 1 was demonstrated by the finding that three unique groups of anti-Cry j 1 mAbs inhibited the binding to Cry j 1 of IgE from the sera of patients with Japanese cedar hypersensitivity (Sakaguchi et al, 1997). However, these epitopes have not been localized to specific structural elements or regions of Cry j 1.…”
Section: Discussionmentioning
confidence: 99%
“…Six monoclonal antibodies (mAbs) against native Cry j 1 (S14, S36, S84, S91, S95 and S131) were described previously (Sakaguchi et al, 1997). These antibodies represent four of the five antibody groups defined by Sakaguchi et al, including the three mAbs groups that competed with the IgE in the sera of Japanese cedar-sensitive patient for binding to Cry j 1.…”
Section: Human Sera and Mouse Mabmentioning
confidence: 99%
See 2 more Smart Citations
“…4) Based on the inhibition of human IgE binding to Cry j 1 by murine monoclonal antibodies, the presence of five independent epitopes was suggested. 5,6) IgE-binding sites on pollen allergens are generally reported to be conformational. 7,8) Taniai et al reported that the inhibitoriest monoclonal antibody (mAb 046) recognized a conformational epitope on Cry j 1.…”
mentioning
confidence: 99%